Did Customers Benefit from the Reorganisation of Customer Management in German Employment Agencies? - Christoph Ehlert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
As a response to an overall high and persistent unemployment rate during the 1990s and the beginning of the new millennium, the German Federal Employment Agency underwent several reforms. One of the most important reforms, the reform of the organisational structure of the Federal Employment Agency, comprised an adjustment of the business model and a reorganisation of placement processes. From 2004 onwards, customer service centres (CSC) and standardised action programmes for diff erent groups of customers were implemented in all German employment agencies, aiming at an improvement of quality and speed in the placement process. By handling customers faster (customer service centres) and activating/supporting them better (action programmes), a higher number of placements into employment should be observed, thus leading to a reduction of unemployment. By taking advantage of the staggered implementation of the customer service centres and action programmes by region, the eff ects on employment rates are estimated. The dynamic difference in- differences approach employed takes into account the time under treatment. The results suggest that the introduction of the customer service centres led to an increase in both, employment infl ows and overall employment, while most of the action programmes had a negative impact on both. – – Als Reaktion auf die hohe und verfestigte Arbeitslosigkeit in der Bundesrepublik in den 1990er Jahren wurden in der Bundesagentur für Arbeit verschiedene Reformen durchgeführt. Eine der wichtigsten Reformen betraf die Reorganisation der Arbeitsvermittlung durch die sukzessive Einführung der Kundenzentren und Handlungsprogramme in allen Arbeitsagenturen und Jobcentern ab 2004. Diese Neuerungen sollten vornehmlich den Vermittlungsprozess effizienter gestalten und beschleunigen. Insgesamt ist durch diese Maßnahmen eine bessere Aktivierung bzw. Unterstützung und somit eine Verringerung der Arbeitslosigkeit zu erwarten. Der vorliegende Artikel nutzt zur Identifikation der Beschäftigungseffekte die Tatsache, dass die Einführung der Kundencenter und Handlungsprogramme in mehreren Wellen geschah. Die Ergebnisse legen nahe, dass die Einführung des Kundenzentrums einen positiven Effekt auf Übergänge in Beschäftigung hatte, während die Handlungsprogramme einen negativen Effekt ausübten.
Keywords: J68; 330; difference-in-differences; program evaluation; customer service centre; action programmes